Worldwide Traceability of Antibiotic Residues from Livestock in Wastewater and Soil: A Systematic Review - Robles-Jimenez, Lizbeth E.; Aranda-Aguirre, Edgar; Castelan-Ortega, Octavio A.; Shettino-Bermudez, Beatriz S.; Ortiz-Salinas, Rutilio; Miranda, Marta; Li, Xunde; Angeles-Hernandez, Juan C.; Vargas-Bello-Perez, Einar; Gonzalez-Ronquillo, Manuel (My University, 2022)
Simple Summary This work focuses on reviewing research works on antibiotic residues, evaluating antibiotics used in livestock production and their excretion in animal products and in environmental matrices such as water and soil worldwide, according to each of the variables used such as antibiotic family, name, concentration (% and mg/kg or ppm), country, and continent where the residue was found. The main antibiotics used worldwide and in animal production are sulfonamides, tetracyclines, quinolones, penicillin, and cephalosporins. The use of antibiotics in animal production are widely used for disease treatment, health protection, and as growth promoters. Common antibiotics used in veterinary medicine are excreted and eliminated through the sewage system, contaminating water and soil with negative effects on agricultural activities. This systematic review focuses on the trend of research works on antibiotic residues, evaluating antibiotics used in livestock production and their excretion in animal products and in environmental matrices such as water and soil. Our database was composed of 165 articles, reporting the concentration of antibiotic residues found in the environment, livestock (cow, sheep, pig, horse, chicken, rabbit, goat), aquatic and terrestrial animal tissues, animal products (milk and eggs), wastewater, and soil. The documents were obtained from Asia, Africa, North America, South America, Europe, and Oceania. A descriptive analysis of antibiotic residues found worldwide was analyzed according to each of the variables used such as antibiotic family, name, concentration (% and mg/kg or ppm), and country and continent where the residue was found. The descriptive analysis was carried out using the "describe" function of psych package and pirate plots were drawn. According to our study, the main antibiotics used worldwide in animal production are sulfonamides, tetracyclines, quinolones, penicillin, and cephalosporins. At present, despite the trends of increased regulations on the use of antibiotics worldwide, antibiotics are still utilized in food animal production, and are present in water and soil, then, there is still the misuse of antibiotics in many countries. We need to become aware that antibiotic contamination is a global problem, and we are challenged to reduce and improve their use.
Keywords: antibiotic residues; livestock; wastewater; antimicrobial resistance; soil residues